Horseradish Peroxidase-modified Single-walled Carbon Nanotubes as Biocathode for Assembling a Membrane-less Glucose-H2O2 Biofuel Cell - Shu, Tong; Gao, Bowen; Yang, Hankun; Su, Lei; Zhang, Xueji (Current Nanoscience, 2016)
Background: Fluorescent film sensors utilizing immobilized fluorescent reporters possess more favorable properties from a practical viewpoint. Recent advances in fluorescent noble metal nanoclusters, e.g. Au and Ag, have greatly prompted the development of fluorescent film sensors. The aims of this paper are to introduce readers to the synthesis of Au and Ag fluorescent nanoclusters and the fabrication of the fluorescent film sensors, and to review research related to the potential application of the nanoclusters-based fluorescent film sensors. Methods: The synthesis of Au and Ag fluorescent nanoclusters, fabrication of fluorescent metal nanocluster film sensors and their application are reviewed. Outlook of the fluorescent film sensors is provided. Results: Au and Ag fluorescent nanoclusters can be synthesized by using different ligands,such as thiol-based ligands, polymers and dendrimers, proteins, etc. Fluorescent films based on nanoclusters can be fabricated by incorporation of the pre-synthesized nanoclusters into the films or direct generation of nanoclusters within the films. Fluorescent film sensors have been used to sensitively and selectively detect heavy metal ions (e.g., Hg2+, Cu2+), nitrite anion, and trinitrotoluene (TNT). Conclusion: Organic ligand shells of nanoclusters play a crucial role in stabilizing Au and Ag nanoclusters and impart the properties of the ligands to the encapsulated nanoclusters. The ligand shells of nanoclusters can be tailored independently, constituting versatile platforms for the development of simple and facile methods of immobilizing nanoclusters on solid substrates. Designing the immobilization strategy of clusters on substrates would have a profound effect on the construction of fluorescent nanocluster film sensors with optimal properties.
Keywords: horseradish peroxidase